Associação entre CMMI-DEV 1.2 e ISO/TS 16949 - Albanez, Altamar Urbanetz de Araújo (2012)
The automotive sector is one of the most daring in terms of quality, requiring because of that certification to ISO/TS 16949. Although these companies dominate this certification, some lose in the subsequent audits or get little improvement beyond existing. There is evidence that they do not have the maturity to obtain or maintain such certification or guidelines to continually improve. In previous work, it was found out that certified companies had at least level 2 maturity, 1 (minimum) and 5 (maximum), which means a company defined and manageable process. However, what enables the company to improve its indexes have the process is controlled and integrated. The lack of maturity of a product development process (PDP) triggers scrap and rework, compromising the efficient use of resources, impacting the time and cost of development and, indirectly, the quality of the process and final product. However, the guidelines do not have certified companies to improve their processes. For this, the ISO would require some resource associated in order to provide guidance on the aspects that need to be improved. Whereas CMMI is an effective method for obtaining diagnostic and maturity that considers the integration of PDP, this work aims to identify the association between the ISO/TS 16949 and CMMI-DEV 1.2 method. Presenting an overview of PDPs, quality certification and process maturity. Later, associated variables are involved in a process of ISO 9001 certification and the variables evaluated in the ISO/TS 16949 with the variables involved in assessing the maturity level 2 with CMMI-DEV 1.2. The paper explains which items are considered by the ISO/TS 16949, CMMI highlighting items that could be used for diagnosis complement for companies that wish to improve the quality factor, adding, in parallel, more efficiency and productivity of their production processes.